LC-DAD Determination of Fleroxacin in Bulk and Pharmaceutical Dosage Forms - Salgado, Hérida Regina Nunes [UNESP]; Moreno, Andreia [UNESP]; Garg, Sanjay (Vieweg, 2009)
Fleroxacin is a third generation fluoroquinolone with broad spectrum antibacterial activity. In this work an LC-DAD method for the analysis of fleroxacin was developed and validated using UV detection at 286 nm. The method was validated for linearity, precision, robustness, LOD, LOQ, specificity and accuracy at concentrations of 0.2-20.0 mu g mL(-1) and r (2) = 1. The LOD and LOQ were 0.059 and 0.197 mu g, respectively, the recoveries were 99.92-102.0% and the CV was less than 2.0%. The LC-DAD validated method provided analytical sensitivity, specificity and reproducibility suitable for quality control analysis.
Keywords: Column liquid chromatography; Liquid chromatography-diode array detection; Quality control; Fleroxacin